Postoperative vascular complications in unrecognised Obstructive Sleep apnoea (POSA) study protocol: an observational cohort study in moderate-to-high risk patients undergoing non-cardiac surgery. Issue 1 (9th January 2014) - Chan, Matthew T V; Wang, Chew-Yin; Seet, Edwin; Tam, Stanley; Lai, Hou-Yee; Walker, Stuart; Short, Timothy G; Halliwell, Richard; Chung, Frances; ,
Abstract : Introduction: Emerging epidemiological data suggest that obstructive sleep apnoea (OSA) is common in the general surgical population. Unfortunately, the majority of these patients are unrecognised and untreated at the time of surgery. There is substantial biological rationale to indicate that patients with unrecognised OSA are at a higher risk of postoperative vascular events. However, the extent of this morbidity is currently unknown. We have initated the p ostoperative vascular complications in the unrecognised o bstructive s leep a pnoea (POSA) study to determine the associations between OSA, nocturnal hypoxia and major postoperative vascular events in 1200 moderate-to-high risk patients undergoing major non-cardiac surgery. Methods and analysis: The POSA study is an international prospective observational cohort study. Using a type 3 portable sleep monitoring device and ambulatory oximetry, we will quantify the severity of OSA. The primary outcome is a composite of vascular death, myocardial infarction; non-fatal cardiac arrest; stroke; pulmonary embolism; congestive heart failure and new arrhythmia within 30 days of surgery. As of November 2013, we have recruited over 700 patients from nine centres in six countries. The mean age is 68 years, the mean body mass index is 27 kg/m 2 and 55% of patients are men. 27.9% of patients have known coronary artery disease, over 76% have diabetes. The majority of patients underwent orthopaedic surgery (28%) and colorectal resection (18.5%). Ethics and dissemination: The POSA study has received ethics approval from all study sites before patient recruitment. Informed consent will be obtained from all patients. The POSA study will determine the risk of unrecognised OSA in major non-cardiac surgery. We will publish these findings in peer-reviewed journals. Trial Registration: ClinicalTrials.gov Identifier: NCT01494181